Functional activity of CD34-positive cells in chronic myeloid leukemia patients with different response to imatinib therapy - Sviezhentseva, I.O.; Perekhrestenko, T.P.; Bilko, D.I.; Gordienko, A.I.; Diachenko, M.V.; Dyagil, I.S. (Experimental Oncology, 2015)
Introduction: It is believed that the reason of the leukemic clone cell resistance to treatment with tyrosine kinase inhibitors during chronic myeloid leukemia (CML) is mutations in the genome of an early bone marrow progenitor cells that are CD34-positive. Such cells, regardless of treatment, acquire ability to proliferation and differentiation. This leads to the re-expansion of the CD34⁺ cells. Aim: to determine the CD34 antigen expression in bone marrow and peripheral blood cells in CML patients with different response to imatinib therapy using the results of hematopoietic cells culturing and the data of flow cytometry. Methods: Bone marrow aspirate from 39 patients who were treated with imatinib was studied with cytogenetic, flow cytometry and culture methods in vitro. Results: In patients with an optimal response to imatinib therapy the number of colonies was 1.8 times lower than the number of those in the group of patients with a suboptimal response to therapy. In turn, in patients with failure of imatinib therapy the number of colonies was the highest and was 2.1 times higher than the patients with optimal response. The results of cytometric studies have shown that the number of CD34⁺ cells in bone marrow was significantly higher compared to the number of CD34⁺ cells in peripheral blood cells and increased with the acquisition of leukemic cells the resistance to imatinib. There was a direct correlation between the number of colonies and clusters in semisolid agar in vitro and the number of CD34⁺ cells in the bone marrow of patients. Conclusions: The correlation between the number of CD34⁺ cells and the number of cell aggregates in semisolid agar in vitro indicates the prognostic value of the method for determining CD34⁺ cells in the patient bone marrow. The parallel increase of their number in the peripheral blood will allow developing express methods for the detection of individual patient response to imatinib therapy. Key Words: chronic myeloid leukemia, imatinib, cell culture in vitro, CD34⁺ cells.